2015
DOI: 10.1002/pssa.201431777
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring thermoelectric properties of nanostructured crystal silicon fabricated by infrared femtosecond laser direct writing

Abstract: The periodic nanostructuring of inner part of semiconductors can be successfully accomplished by the infrared ultrashort pulse laser with a double pulse configuration. Self‐organized nanostructures inside semiconductor could be induced empirically only if it is indirect band gap semiconductor. The strained silicon regions with a width of about 100 nm are self‐aligned parallel to the polarization direction of the first arriving pulses, despite of the polarization direction of the secondly arriving pulses. AFM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
7
31
0
Order By: Relevance
“…They demonstrated the generation of polycrystalline and amorphous silicon at silicon surfaces affected by ns, ps, and fs laser pulses, respectively. Likewise Mori et al., who study nanogratings in Si, see the same behavior in their Raman measurements. Peak‐fitting of the crystalline contribution at 520 cm −1 with a Lorentzian shape and a Gaussian shape for the amorphous contributions at 480 cm −1 as well as for the grain boundaries contributions at 500 cm −1 yield information on the degree of crystallinity .…”
Section: Raman Analysissupporting
confidence: 59%
See 2 more Smart Citations
“…They demonstrated the generation of polycrystalline and amorphous silicon at silicon surfaces affected by ns, ps, and fs laser pulses, respectively. Likewise Mori et al., who study nanogratings in Si, see the same behavior in their Raman measurements. Peak‐fitting of the crystalline contribution at 520 cm −1 with a Lorentzian shape and a Gaussian shape for the amorphous contributions at 480 cm −1 as well as for the grain boundaries contributions at 500 cm −1 yield information on the degree of crystallinity .…”
Section: Raman Analysissupporting
confidence: 59%
“…Within the last two decades, numerous attempts have been performed to overcome these limitations . Recently, localized modifications in the bulk of silicon using ultrashort laser pulses have been demonstrated . This resulted in the first demonstration of waveguides written with fs laser pulses at a wavelength of 1550 nm by Pavlov et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the steep angular components forming our beam (>20 ), we measure that the clamping of the intensity, the subsequent free-carrier density and absorbed energy remain at levels far below the thresholds for local modification in bulk silicon. There is today a general trend toward ultrashort pulses for ultraprecision micromachining applications but our investigations with SWIR femtosecond Bessel beams suggest that only longer pulses 11,12 or multiple pulses 13 can be envisioned for deep micromachining inside silicon.…”
Section: Introductionmentioning
confidence: 96%
“…Periodic nanostructures within the semiconductor can be achieved by an infrared ultrashort pulse laser with a dual pulse configuration. In 2015, M. Mori et al reported that the periodic nanostructures inside the semiconductor caused by infrared ultrashort pulse lasers were generated by a double pulse configuration without surface damage [187]. In 2015, M. Sobhani et al studied irradiated sub-micro/nano structure of polished silicon using double nanosecond laser pulses (λ = 532 nm) in distilled water.…”
Section: Laser-induced Periodic Surface Structurementioning
confidence: 99%